A importância do porto do Itaqui como Hub de combustíveis aos Estados do Maranhão, Tocantins e Piauí - RODRIGUES, Rodrigo Freitas (2024)
The present work aims to highlight the significant relevance of the Porto do Itaqui as a crucial hub in the distribution of fuels to the states of Maranhão, Piauí, and Tocantins. In this context, comprehensive operational data of the port is presented, elucidating details of its infrastructure, emphasizing its strategic connections with the railway and road transport modes, underscoring its strategic location for the international market. Additionally, the logistic involved in fuel movement throughout the port's influence area is explained, highlighting its expansion over the years, and analyzing its participation in the global cargo transportation market. This study seeks to provide a comprehensive understanding of the role played by the Porto do Itaqui in the national and international scenario of fuel logistic.